PSE (Pressurized Solvent Extraction) -tekniikan soveltaminen ja menetelmän kehittäminen viljojen lipidien uuttoon - Aaltonen, Katri Elina, 1979- (Helsinki : Helsingin yliopisto, 2011)
Abstract: Applicability of Pressurized Solvent Extraction (PSE) technique and method development for cereal lipid extraction.
Pro gradu -tutkielma
Keywords: vilja; lipidit; uutto; erotusmenetelmät